#### Answer

x=4

#### Work Step by Step

Simplifying
6x + 2 = 2(17 + -1x)
Reorder the terms:
2 + 6x = 2(17 + -1x)
2 + 6x = (17 * 2 + -1x * 2)
2 + 6x = (34 + -2x)
Solving
2 + 6x = 34 + -2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '2x' to each side of the equation.
2 + 6x + 2x = 34 + -2x + 2x
Combine like terms: 6x + 2x = 8x
2 + 8x = 34 + -2x + 2x
Combine like terms: -2x + 2x = 0
2 + 8x = 34 + 0
2 + 8x = 34
Add '-2' to each side of the equation.
2 + -2 + 8x = 34 + -2
Combine like terms: 2 + -2 = 0
0 + 8x = 34 + -2
8x = 34 + -2
Combine like terms: 34 + -2 = 32
8x = 32
Divide each side by '8'.
x = 4
Simplifying
x = 4